Clinical efficacy of Wenjing decoction in the treatment of ovulatory disorder infertility: A systematic review and meta-analysis. Issue 28 (15th July 2022) - Zuo, Qian-qian; Yu, Zhi-fang; Liu, Meng-rui; Du, Hui-lan
Abstract : Objectives: Wenjing decoction (WJD) was widely used in the treatment for ovulatory disorder infertility (ODI) in China, while its efficacy was not clearly known. In this study, we evaluated the clinical efficacy of WJD by meta-analysis. Methods: Eight electronic databases including Cochrane Library, PubMed, Embase, Web of Science, China National Knowledge Infrastructure, WanFang Data, VIP Database, and China Biology Medicine were searched for randomized controlled trials (RCTs) published from the inception of each database to July 1, 2021, of which the interventions involve WJD and clomiphene. Outcomes included clinical efficacy rate, pregnancy rate, ovulation rate, dominant follicle diameter, endometrial thickness, estradiol, follicle-stimulating hormone, and luteinizing hormone. Meta-analysis and risk of bias were performed by RevMan 5.3 software. Results: Eleven RCTs including 915 patients, of which 476 in the intervention group and 439 in the control group. Meta-analysis showed that WJD was better than clomiphene for patients with ODI in terms of clinical effective rate (odds ratio [OR] = 1.22, 95% confidence interval [CI]: 1.08–1.34), pregnancy rate (OR = 1.54, 95% CI: 1.15–2.07), ovulation rate (OR = 1.34, 95% CI: 1.07–1.67), endometrial thickness (mean difference [MD] = 1.50, 95% CI: 0.90–2.10), and dominant follicle diameter (MD = 1.85, 95% CI: 0.68–3.02). The estradiol level (MD = 91.0, 95% CI: 80.3–101.88) in patients taking WJD was significantly higher than those taking clomiphene, while the follicle-stimulating hormone level (MD = −0.93, 95% CI: −1.13 to −0.72) and the luteinizing hormone level (MD = −4.41, 95% CI: −4.80 to −4.03) in patients taking WJD was significantly lower than those taking clomiphene. Our results also indicated that WJD combined with clomiphene was better than clomiphene alone for patients with ODI in terms of pregnancy rate (OR = 1.79, 95% CI: 1.37–2.35). Conclusions: WJD may be effective in the treatment of patients with ODI. Due to the quality and quantity of literature, RCT with large sample size and high quality need to be performed to verify our conclusion.